Ottawa 2020 consensus statement for programmatic assessment – 1. Agreement on the principles. (3rd October 2021) - Heeneman, Sylvia; de Jong, Lubberta H.; Dawson, Luke J.; Wilkinson, Tim J.; Ryan, Anna; Tait, Glendon R.; Rice, Neil; Torre, Dario; Freeman, Adrian; van der Vleuten, Cees P. M.
Abstract: Introduction: In the Ottawa 2018 Consensus framework for good assessment, a set of criteria was presented for systems of assessment. Currently, programmatic assessment is being established in an increasing number of programmes. In this Ottawa 2020 consensus statement for programmatic assessment insights from practice and research are used to define the principles of programmatic assessment. Methods: For fifteen programmes in health professions education affiliated with members of an expert group ( n = 20), an inventory was completed for the perceived components, rationale, and importance of a programmatic assessment design. Input from attendees of a programmatic assessment workshop and symposium at the 2020 Ottawa conference was included. The outcome is discussed in concurrence with current theory and research. Results and discussion: Twelve principles are presented that are considered as important and recognisable facets of programmatic assessment. Overall these principles were used in the curriculum and assessment design, albeit with a range of approaches and rigor, suggesting that programmatic assessment is an achievable education and assessment model, embedded both in practice and research. Knowledge on and sharing how programmatic assessment is being operationalized may help support educators charting their own implementation journey of programmatic assessment in their respective programmes.